(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper introduces a new class of functions between bitopological spaces, namely contra-(τ_1,τ_2)-continuous functions. Furthermore, several characterizations and some properties concerning contra-(τ_1,τ_2)-continuous functions are investigated.